Ligand-promoted intramolecular dehydrogenative cross-coupling using a Cu catalyst: direct access to polycyclic heteroarenes - Ray, Devalina; Manikandan, T.; Roy, Arup; Tripathi, Krishna N.; Singh, Ravi P. (Chemical Communications, 2015)
A copper(II)-promoted intramolecular C-H coupling reaction between indole-2 and imidazole-2 moieties has been developed for polycyclic heteroarene synthesis. The method provides direct access to biheteroaryl incorporated polycyclic frameworks, which are of huge interest in the area of functional materials and drug-discovery.

Palladium-catalyzed oxidative annulation of pyrrolylalkyl-1H-azoles: towards the synthesis of polyheterocyclic arenes - Tripathi, Krishna N.; Bansode, Avinash H.; Singh, Ravi P. (Synthesis-Stuttgart, 2020)
A highly efficient and regioselective palladium-catalyzed annulation protocol for a series of linear and terminally substituted 1,2- and 1,3-di(heteroaryl)alkanes to the corresponding polyheterocyclic arenes is reported. Herein, intramolecular oxidative coupling involving double C(sp(2))-H bond functionalization provides a feasible access to biheteroaryl systems annulated to a six-membered ring. The methodology is not restricted to six-membered annulations and was extended to the synthesis of compounds with a seven-membered ring and biheteroaryl core.
Keywords: C-H functionalization; imidazoles; oxidative coupling; Palladium; pyrroles